New Insights in Saccharomyces cerevisiae Response to the Cyanotoxin Microcystin-LR, Revealed by Proteomics and Gene Expression - Valério, Elisabete (2021)
This article belongs to the Special Issue Advances in the Toxicity Mechanisms of Microcystins Revealed by Omics Approaches